2018
DOI: 10.1017/s0014479718000017
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Major Determinants of Rice Production and Farmers’ Choice of Rice Ideotypes in South Sudan: Implications for Breeding and Policy Interventions

Abstract: SUMMARYRice (Oryza sativa L.) is an important staple crop in South Sudan. Current rice consumption in the country is approximately 23,000 mg year−1 of which more than 75% is imported. We investigated farmers’ perceived rice production and productivity constraints and choice of rice ideotypes across rainfed and irrigated rice agro-ecologies in South Sudan to guide breeding and policy interventions. Data were gathered through participatory rural approaches and a formal structured survey involving 136 rice farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…A combination of matrix scores using a modified scale and preference ranking logistic regressions showed that improved rice varieties; NamChe 4, NamChe 5 and E22 had significantly high probability of acceptance because these varieties had the qualitative and quantitative attributes required by farmers under their production and marketing conditions. The key attributes that influenced upland rice variety acceptance in the current study included; drought tolerance, early maturity period, yield, panicle size and grain filling, but elsewhere, studies have shown that consumer preferred improved rice varieties developed based on information derived through participatory variety selection may increase production, utilization and marketability [28]. Although local upland rice varieties were agronomically low performing and ranked least in the current study, farmers continue to grow them mainly because of high drought tolerance and early maturity period.…”
Section: Discussionmentioning
confidence: 86%
“…A combination of matrix scores using a modified scale and preference ranking logistic regressions showed that improved rice varieties; NamChe 4, NamChe 5 and E22 had significantly high probability of acceptance because these varieties had the qualitative and quantitative attributes required by farmers under their production and marketing conditions. The key attributes that influenced upland rice variety acceptance in the current study included; drought tolerance, early maturity period, yield, panicle size and grain filling, but elsewhere, studies have shown that consumer preferred improved rice varieties developed based on information derived through participatory variety selection may increase production, utilization and marketability [28]. Although local upland rice varieties were agronomically low performing and ranked least in the current study, farmers continue to grow them mainly because of high drought tolerance and early maturity period.…”
Section: Discussionmentioning
confidence: 86%
“…It will fast-track the attainment of SDGs target of eradicating hunger by 2030. Thus, to complement the government's action, research is key to finding solutions (Bennett, 2014;Mogga et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the above issues amongst others peculiar to rice farmers reinforce the need to assess the determinants of rice production from a geosocial perspective. It has been reported that labour hours, urea fertilizers, and irrigation significantly bolster rice yield in Pakistan (Ali et al, 2022) Some authors have cited factors that militate against rice productivity to include poor infrastructure, insufficient or unavailability of irrigation facilities, unavailability of high yielding varieties, unreliable rainfall, importation as well as difficulty in sourcing machinery and funding (Ita et al, 2013;Kadiri et al, 2014;Koirala et al, 2014;Onyekwena, 2016;Tanko et al, 2016;Adenuga et al, 2016;Ugalahi et al, 2016;Niang et al, 2017;Mogga et al, 2019;Hayat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa L.) is an important food crop that has grown to be a significant cash crop in Uganda (Kijima and Otsuka, 2017) and in particular, the more preferred aromatic rice (Mogga et al, 2018) reported to offer supplementary health benefits (Prodhan et al, 2017). The utilization of the crop has also broadened in different industries such as food manufacturing (Plengsaengsri, 2019), health (Sen et al, 2020), energy (Olupot et al, 2015;Menya et al, 2018) and the construction sector (Yiga et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although rice grain qualities differ around the world, long and slender shape of rice grains is preferred in Africa (Asante, 2017). Rice aroma, characterized by the sweet popcorn smell (Buttery, 1983), in both raw and cooked grains is the most important trait (Mogga et al, 2018). In addition, the rice grain traits such as grain shape defined by the ratio of grain length to the grain width (Singh et al, 2000) is considered important (Kitara et al, 2018) with preference mostly for slender grain shape.…”
Section: Introductionmentioning
confidence: 99%